Cadmium sulfide thin films for flexible solar cell received by magnetron dispersion method - Zaitsev, Roman Valentinovich; Kirichenko, Michailo Valerievich; Khrypunov, Gennadiy Semenovich (Національний технічний університет "Харківський політехнічний інститут", 2018)
For the purpose of creation of the economic, suitable for large-scale application technology of formation of a layer of wide-scale "window", for thin-film photo-electric converters on the basis of sulfide and telluride of cadmium the pilot studies of temperature effect of a deposition of the films of sulfide of cadmium received by method of magnetron dispersion on a direct current on their optical properties and crystalline structure were conducted. By method of a two-channel optical spectroscopy it is established that a deposition of films of sulfide of cadmium at a temperature of 160 °C allows to form layers with a width of forbidden region of 1,41 eV that approaches value, characteristic of monocrystals, a nd the density of the photon flux passing through a cadmium sulfide layer in a spectral interval of a photosensitivity of telluride of cadmium at the level of 37,0 W·nm·cm2. Body height of precipitation temperature to 160 °C leads to decrease in optical losses in cadmium sulfide films, as a result of increase in the sizes of areas of a coherent scattering and decrease of level of macrodeformations. At further increase of precipitation temperature up to 230 °C the defining factor leading to growth of optical losses in cadmium sulfide films becomes their imp overishment by an easily volatile component – sulfur.

З метою створення економічної, придатної для широкомасштабного застосування технології формування шару широкозонного «вікна» для тонкоплівкових фотоелектричних перетворювачів на основі сульфіду та телуриду кадмію були проведені експериментальні дослідження впливу температури осадження плівок сульфіду кадмію, отриманих методом магнетронного розпилення на постійному струмі, на їх оптичні властивості і кристалічну структуру. Методом двоканальної оптичної спектроскопії встановлено, що осадження плівок сульфіду кадмію при температурі 160 °С дозволяє формувати шари з шириною забороненої зони 1,41 еВ, що наближається до значення, характерного для монокристалів, і щільністю потоку фотонів, що проходять через шар сульфіду кадмію в спектральному інтервалі фоточутливості телуриду кадмію, на рівні 37,0 Вт•нм•см2.
Тонкі плівки сульфіду кадмію для гнучких сонячних елементів, отримані методом магнетронного розпилення
Keywords: optical losses; width of the forbidden region; crystalline structure; оптичні втрати; ширина забороненої зони; кристалічна структура